THE INFLUENCE OF ORGANIZATIONAL CHANGE AND CAREER ADAPTABILITY ON EMPLOYEE PERFORMANCE MEDIATED BY JOB SATISFACTION AT THE REGIONAL OFFICE OF THE MINISTRY OF HUMAN RIGHTS OF CENTRAL JAVA - Vandiga Luksi Almahatma; Dewie Tri Wijayati Wardoyo; Jun Surjanti (Universitas Nusa Cendana, 2025)
This study aims to examine and analyze the influence of organizational change and career adaptability on employee performance, mediated by job satisfaction, at the Regional Office of the Ministry of Human Rights in Central Java. The population of the study includes 66 employees of the aforementioned office. A quantitative method is employed, using Structural Equation Modelling (SEM) with a Partial Least Squares (PLS) approach. The results reveal that both organizational change and career adaptability have a positive and significant effect on job satisfaction. Organizational change also has a direct and significant impact on employee performance, while career adaptability does not directly affect performance. However, job satisfaction significantly mediates the influence of both organizational change and career adaptability on employee performance. These findings highlight the crucial role of job satisfaction as an intervening mechanism in improving employee performance, particularly within public organizations undergoing transformation and demanding a high level of career adaptability from their personnel. Keywords : Career Adaptability; Job Satisfaction; Employee Performance; Organizational Change